A Final Word on Train Wrecks. Issue 1 (2nd January 2021) - Sherman, Jeffrey W.; Rivers, Andrew M.
Abstract: We identify the main themes raised in the commentaries and respond. To summarize: Yes, there were problems with social priming (and most other psychological) research; yes, the definition of social priming matters; no, cherry-picking specific studies to replicate does not amount to a systematic examination of the relevant research; yes, within-subjects social priming studies are robust; yes, it is wrong to conflate research reproducibility and misconduct; and, yes, it was personal.